Kemapanan Burung Bentet Kelabu (Lanius schach) Asal Yogyakarta di Pulau Salibabu [The Establishment of Gray Bentet Bird (Lanius schach) from Yogyakarta in Salibabu Island] - LALA, FREDY (Buletin Palma, 2016)
The Gray Bentet bird (Lanius schach) is one of the potential predators as biological agents against grasshopper pests. As many as 30 males and 10 females of the Gray Bentet birds had been introduced from Yogyakarta to Salibabu Island, Talaud Islands Regency, North Sulawesi Province, for controlling coconut pest namely Sexava nubila grasshopper.  The establishment, development, and biology of the Gray Bentet birds were studied at District of Moronge in Salibabu Island, from August 2011 to July 2012. Establishment of the Gray Bentet bird was indicated by its population, dispersal, and the resulted new generation. Results showed that the Gray Bentet bird was very successfully established and well developed in Salibabu Island. At 3 months after release as many as 20 birds were rediscovered and they had dispersed as far as 6 – 15 km away from the release site. The new generation of as many as 2 birds were discovered at 9 months after releasing of their parents. Biology of the Gray Bentet birds in Salibabu Island was similar with that in their origin in Yogyakarta. A single female produced 4 eggs per reproductive period for 3-4 days, with sex ratio of 3 males : 1 female. Producing eggs frequency was twice per year. The first mating occurred when the Gray Bentet birds was at 9 months old. The Gray Bentet bird belonged to  insectivorous group, diurnal birds, and it attacks moving preys. The predatory bird developed well in Salibabu Island and it was a promising biological control agent against the pest of S. nubila.ABSTRAKBurung Bentet kelabu Lanius schach merupakan salah satu predator yang berpotensi sebagai agens hayati hama belalang. Sebanyak 30 ekor burung jantan dan 10 ekor betina telah diintroduksikan dari Yogyakarta ke Pulau Salibabu, Kabupaten Kepulauan Talaud, Provinsi Sulawesi Utara, untuk pengendalian hama kelapa, belalang Sexava nubila. Kemapanan, perkembangan, dan biologi burung ini dikaji di Kecamatan Moronge, Pulau Salibabu, sejak bulan Agustus 2011 sampai Juli 2012. Kemapanan burung L. schach diukur berdasarkan populasi, pemencaran, dan generasi baru. Hasil kajian menunjukkan bahwa burung L. schach  berhasil mapan dan berkembang dengan baik di Pulau Salibabu. Pada tiga bulan sesudah pelepasan sebanyak 20 ekor ditemukan kembali dan telah memencar sejauh 6-15 km dari tempat pelepasan. Burung generasi baru sebanyak 2 ekor ditemukan pada saat 9 bulan setelah pelepasan induknya. Biologi L. schach di Pulau Salibabu mirip dengan di daerah asalnya Yogyakarta. Seekor betina bertelur sebanyak 4 butir/periode bertelur. Masa bertelur selama 3-4 hari. Frekuensi bertelur  dua kali per tahun. Sex ratio 3 jantan : 1 betina. Burung L. schach kawin pertama kali saat berumur sekitar 9 bulan. Burung ini termasuk golongan pemakan serangga, aktif pada siang hari, dan memburu mangsa yang bergerak. Burung predator ini berkembang dengan baik dan merupakan agens pengendalian hayati yang menjanjikan terhadap hama S. nubila di Pulau Salibabu.